Lymphoma of Ovary: A Primary Extra-nodal Manifestation - Joshi, AP; Chitrakar, NS; Shrestha, I (Nepal Journal of Obstetrics and Gynaecology, 2015)
Involvement of the ovary by malignant lymphoma is a well-known manifestation of disseminated nodal disease. But, lymphoma as primary manifestation is extremely rare. Here, we report a case of malignant lymphoma which presented as ovarian cancer and managed with surgery and subsequent chemotherapy. A lady of thirty two years presented with features of malignant ovarian tumor. The diagnosis of malignant ovarian lymphoma was made after surgery and histological and immunohistochemical study of the excised tumor. The tumor was classified as diffuse large B-cell lymphoma. The patient was put on chemotherapy and she is on follow-up in disease free-state for last two years.